Background on the state of agricultural negotiations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
An ICTSD/IISD Briefing on the negotiations on Agriculture at the WTO since Doha...